Experimental Study of Thoracoabdominal Injuries Suffered from Caudocephalad Impacts Using Pigs. (10th May 2018) - Guan, Sishu; Liao, Zhikang; Xiang, Hongyi; Zhu, Xiyan; Wang, Zhong; Zhao, Hui; Liu, Peng; Lai, Xinan
Abstract : To know the caudocephalad impact- (CCI-) induced injuries more clearly, 21 adult minipigs, randomly divided into three groups: control group (n = 3 ), group I (n = 9 ), and group II (n = 9 ), were used to perform the CCI experiments on a modified deceleration sled. Configured impact velocity was 0 m/s in the control group, 8 m/s in group I, and 11 m/s in group II. The kinematics and mechanical responses of the subjects were recorded and investigated. The functional change examination and the autopsies were carried out, with which the injuries were evaluated from the Abbreviated Injury Scale (AIS) and the Injury Severity Score (ISS). The subjects in group I and group II experienced the caudocephalad loading at the peak pelvic accelerations of 108.92 ± 58.87 g and 139.13 g ± 78.54 g, with the peak abdomen pressures, 41.24 ± 16.89 kPa and 63.61 ± 65.83 kPa, respectively. The injuries of the spleen, lung, heart, and spine were detected frequently among the tested subjects. The maximal AIS (MAIS) of chest injuries was 4 in group I and 5 in group II, while both the MAIS of abdomen injuries in group I and group II were 5. The ISS in group II was 52.71 ± 6.13, significantly higher than in group I, 26.67 ± 5.02 (p < 0.05 ). The thoracoabdomen CCI injuries and the mechanical response addressed presently may be useful to conduct both the prevention studies against military or civilian injuries.